DEVIANT POLYGAMY PRACTICES AND ITS IMPACT ON WOMEN AND CHILDREN: A CRIMINAL LAW ANALYSIS - Edwar, Frand; Mukhlishin, Ahmad; Muslih, M; Hidayat, Sarif (Universitas Islam Negeri Raden Intan Lampung, 2022)
Polygamous marriages can be carried out by first fulfilling the requirements as stipulated in the legislation. But in fact, there are cases of polygamous practices being carried out not in accordance with statutory regulations, and not obtaining permission from the Court, the practice of polygamous marriages is carried out secretly without the knowledge of the first wife and is carried out in sirri. The purpose of this article is to analyze the factors that led to the practice of polygamy in Notoharjo Village, Kec. Trimurjo Kab. Central Lampung, then the implications of deviant polygamy behavior on household harmony and whether deviant polygamous behavior can be punished. This type of article is qualitative, with a case study approach that is analyzed from a criminal law perspective. The primary data source for this article is the perpetrators of deviant polygamy. Data collection techniques through observation, interviews and documentation. The results showed that the factor of deviant polygamy was due to an affair that the first wife did not want to know about. The implications of deviant polygamous marriages are that they result in damage to harmony in the household, and deviant polygamous practices can be subject to criminal sanctions.Keywords: Deviant Polygamy, Implications and Criminal Sanctions.